2015
DOI: 10.1007/s10450-015-9684-6
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent adsorption of biogas compositions containing CO2, CH4 and N2 on Maxsorb and Cu-BTC using extended Langmuir and Doong–Yang models

Abstract: Upgrading raw biogas and landfill gas to methane purity [98 % is a vital prerequisite for the utilization of biogas for compressed natural gas pipeline applications. Pressure swing adsorption (PSA) is an industrial separation technology widely used for the separation and purification of methane rich streams from raw biogas and landfill gas. Current PSA technologies make use of differential adsorption of gases on traditional adsorbents, such as zeolites, activated alumina and molecular sieves. In order to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The pore structure parameters, such as the specific surface area, meso pore volume and micro pore volume of the HKUST‐1 and HKUST‐1@AC composites are summarized in Table . Compared to the HKUST‐1, the BET surface area and micro pore volume for all the HKUST‐1@AC composites increase, and the HKUST‐1@AC/2% gave the maximum specific surface area of 1145.71 m 2 /g and micro pore volume of 0.4363 mL/g, which have been proved to be the key factors for AC in CO 2 adsorption in previous studied ,. We also found that the specific surface area of HKUST‐1@AC/3% decreased sharply, compared with HKUST‐1@AC/1% and HKUST‐1@AC/2%, which might be due to the changed morphology and the obvious structural defects.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The pore structure parameters, such as the specific surface area, meso pore volume and micro pore volume of the HKUST‐1 and HKUST‐1@AC composites are summarized in Table . Compared to the HKUST‐1, the BET surface area and micro pore volume for all the HKUST‐1@AC composites increase, and the HKUST‐1@AC/2% gave the maximum specific surface area of 1145.71 m 2 /g and micro pore volume of 0.4363 mL/g, which have been proved to be the key factors for AC in CO 2 adsorption in previous studied ,. We also found that the specific surface area of HKUST‐1@AC/3% decreased sharply, compared with HKUST‐1@AC/1% and HKUST‐1@AC/2%, which might be due to the changed morphology and the obvious structural defects.…”
Section: Resultssupporting
confidence: 53%
“…Adsorption and storage of CO 2 in various MOF have gained increasing interests recently and many of the several research papers were published to improve CO 2 adsorption capacity . Results from different reviewers have demonstrated that the interaction force between the gas molecules and the MOFs material is the key factor of the adsorption, and combing with specific material could improve this performance ,. In every case, the applicability and other performance of an MOF can be further functionalized by constructing composite with suitable materials.…”
Section: Introductionmentioning
confidence: 99%
“…Here, is the absolute adsorption of th component of the mixture, max the maximum absolute adsorption corresponding to saturation pressure , the characteristic energy of adsorption, the measure of the pore heterogeneity of the microporous material [31][32][33], the ideal gas constant, the temperature, and the gas pressure. The measured excess adsorptions of pure gases are converted into absolute adsorption using [34]…”
Section: Mass and Energy Balance The Total Mass Balance In The Breakmentioning
confidence: 99%
“…Further details of DYM are available in Doong and Yang, Rege et al [4,36], and the authors' previous work [34]. The energy balance equation for the column (fluid and the solid phase) is given by the following equation:…”
Section: State Equation (Eos)mentioning
confidence: 99%
“…In order to enhance the adsorption performance of Cu‐BTC, the assembly can be altered by additional materials . Because of the low thermal conductivity of Cu‐BTC, the adsorption loading of the system is limited . In this study, multiwalled carbon nanotubes (MWCNTs) were chosen as modifying materials for Cu‐BTC.…”
Section: Introductionmentioning
confidence: 99%